The Influence of Digital Literacy, Business Accessibility, and Illegal Parking on the Development of Small and Medium Culinary Enterprises in the Asia Mega Mas Area, Medan - Agusman Agusman; Leony Hoki; Lisbeth Vanessa Marrimarshel (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2026)
This study aims to describe the influence of digital literacy, business accessibility and illegal parking on the development of small and medium culinary MSMEs in Asia Mega Mas Medan. The research methodology used is a quantitative descriptive method. The type of data used in this study is quantitative data, which is data obtained in the form of numbers or figures. The data sources are in the form of primary data and secondary data. Primary data was obtained from the results of the distribution of questionnaires to respondents, secondary data was obtained from data and literature related to the problems discussed. The population in this study is all small and medium culinary MSME actors in Asia Mega Mas which totals 136 respondents. The sampling technique used is accidental sampling where 102 respondents from MSMEs will be randomly selected as research samples. The results of the research analysis show that Digital Literacy has an effect on the Development of MSMEs in Asia Mega Mas Medan. Business Accessibility has an effect on the Development of MSMEs in Asia Mega Mas Medan. Illegal Parking Affects the Development of MSMEs Asia Mega Mas Medan. Digital Literacy, Business Accessibility, Illegal Parking have an effect on the Development of MSMEs Asia Mega Mas Medan.